Evidence that transverse variability of critical current density can greatly mitigate screening current stress in high field REBCO magnets - Jeseok Bang; Jonathan Lee; Griffin Bradford; Kwangmin Kim; Xinbo Hu; Dmytro Abraimov; Jan Jaroszynski; Anatolii Polyanskii; So Noguchi; Seungyong Hahn; David C. Larbalestier (Scientific Reports)
Abstract Plastic damage of REBCO (REBa2Cu3O7-x, where RE=rare earth) coated conductors by screening current stress (SCS) is a significant concern for ultra-high-field superconducting magnets. Indeed, the third Little Big Coil (LBC3), a REBCO magnet that generated a record, high field of 45.5 T, showed wavy plastic damage produced by excess SCS in all pancakes except two made with single-slit conductors having their slit edges pointing inward towards the magnet center. Reasons for this slit edge orientation-dependent damage mitigation having not yet been presented, we made it the central issue of this new Little Big Coil (LBC4). Accordingly, we constructed and tested LBC4 by replicating LBC3, except that only single-slit tapes were used and every slit edge pointed inward towards the magnet center. LBC4 reached 44.0 T without quench but with some dissipation. After a small lowering of the current without disappearance of the dissipation, the current was charged again, resulting in a quench at 43.5 T due to excess heating in one pancake-to-pancake joint. Indeed, LBC4 exhibited much less wavy conductor damage than LBC3, demonstrating significant SCS mitigation. Detailed post mortem showed a transverse variation of critical current density ( $$J_c$$ ) across the LBC4 conductor, $$J_c$$ being highest at the slit edge and lowest at the not-slit edge. Our computed screening current stresses were markedly lowered by this $$J_c$$ gradient. This paper shows the importance of considering such transverse $$J_c$$ variability, which has not previously been considered, in the precise stress analysis of ultra-high-field REBCO magnets.